Convoluted ν-Signals on 114Cd Isotope from Astrophysical and Laboratory Neutrino Sources - Vaitsa Tsakstara (Advances in High Energy Physics)
At first, we evaluate scattering cross sections of low, and intermediate-energy neutrinos scattered off the 114 Cd isotope, the most abundant Cd isotope present also in the COBRA detector (CdTe and CdZnTe materials) which aims to search for double beta decay events and neutrino observations at Gran Sasso laboratory (LNGS). The coherent ν-nucleus channel addressed here is the dominant reaction channel of the neutral current ν-nucleus scattering. Our ν-nucleus cross sections (calculated with a refinement of the quasiparticle random-phase approximation, QRPA) refer to the gs→gs transitions for ν-energies εν≤100 MeV. Subsequently, simulated ν-signals on 114 Cd isotope are derived. Towards this purpose, the required folded cross section comes out of simulation techniques by employing several low, and intermediate-energy neutrino distributions of the astrophysical ν-sources, like the solar, supernova, and Earth neutrinos, as well as the laboratory neutrinos, the reactor neutrinos, the pion-muon stopped neutrinos, and the β-beam neutrinos.